EFL Young Learners’ Perception of Vocabulary Teaching Through Snowball Throwing Technique - Sakhi Herwiana (Peneliti.net, 2023)
The aim of this study is to investigate young learners’ perception of the snowball-throwing technique in teaching vocabulary. The research used a qualitative research method and the participants were the fifth graders in the public elementary school, in East Java. The result showed that the implementation of the snowball-throwing technique in teaching vocabulary can help students to learn English. They enjoyed learning English with this technique and they felt more active in participation, happy, and confident in learning activities.